Candied kalamansi (Citrus microcarpa Bunge) packaging and product development - Urgel, Petronela Y.; Gatchalian, Miflora M. (1988.)
A standardized process for dehydrated candied kalamansi was developed from the ripe fruit (Citrus microcarpa Bunge). the variables studied were the syruping method, soaking time, and final moisture content. Evaluation of the methods and treatment involved several objective and sensory tests. These included measurement of % moisture content, % soluble solids content, and sensory evaluation of the finished product for appearance, color, flavor, texture, and general acceptability. Results of the objective and sensory tests showed that the best candying procedure involved the utilization of the step-up method (40-50-60°Bx), and the use of overnight soaking time. The optimum moisture level was determined to be 10-12%. Pre-treatments such as soaking in 10% brine and 10-minute boiling of kalamansi slices were necessary to remove the bitter taste of the peels. Addition of the extracted juice into the syrup and cooling of the syrup to 40°C before soaking improved flavor and color retention. Packaging studies were also done on the product. This involved the determination of the Sorption Isotherm, Critical Moisture Content, and Maximum Allowable Water Vapor Transmission Rate. From the results, the best suited packaging material was determined to be High Density Polyethylene (HDPE).
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Kalamansi, Candied -- Packaging